RESPON KECAMBAH PADI (Oryza sativa L.) SOLOK TERHADAP CEKAMAN GARAM - Rahmi Anandia; Dewi Indriyani Roslim; Herman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The salt-stress tolerant rice genotypes are very important to overcome the salt stress in coastal area. This study was aimed to analyze the responses of shoot and root of rice seedlings to the salt stress. The rice genotype (Solok) tested was originally from Kecamatan Bantan, Kabupaten Bengkalis. This study was conducted using Randomized Block Design with three replications. The rice was treated with different salt concentrations, i.e 0 mM (control), 15 mM, 30 mM, and 45 mM. The results showed that the root growth and biomass of Solok genotype was not significantly different between various treatments. This happened because the salt concentration was low. Similarly with the root growth and biomass, the shoot growth and biomass of Solok genotype was not significantly different between various treatments of the salt-stress.